Delineating Somatostatin's Neuronal Actions - Blake, A. D.; Badway, A. C.; Strowsk, M. Z. (Current Drug Targets-CNS & Neurological Disorders, 2004)
Somatostatin (somatotropin release inhibitory factor; SRIF) initiates its biological activity by interacting with a family of highly homologous integral membrane receptors (sst1 -sst5). SRIF neuronal actions regulate protein phosphorylation levels, control second messenger production and modulate neuronal membrane potential. Recently, our understanding of SRIF neurobiology has been driven by new pharmacological and molecular biological tools. SRIF receptor subtype specific antibodies have identified a distinctive, yet overlapping, expression pattern for this receptor family, with multiple subtypes co-localizing in the central and peripheral nervous system. This complex expression profile has confounded efforts to establish each receptor's role in the nervous system in part by the possible homo- and heteroligomerization of the receptor proteins. However, the recent discovery of SRIF receptor subtype selective ligands, supplemented by in vitro and in vivo models with inactivated SRIF receptor genes, now provides opportunities to clearly delineate each receptor's neuronal role. The convergence of these pharmacologic, immunologic and molecular biologic approaches extend our understanding of SRIF neurobiology while promising new therapeutic avenues for SRIF research.
Keywords: parkinsons disease